Iowa RBA, September 2, 1996 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1996)
Iowa RBA update for September 2, 1996. Highlights of the update include sightings of Red-necked Phalaropes and Little Blue Herons. Other interesting observations were of a family of Blue Grosbeaks, 350 Cattle Egrets, and an Olive-sided Flycatcher. Also included are handwritten notes for the next week's update with sightings of 8 American Golden-Plovers and a Buff-breasted Sandpiper. Epson - sheet feed/flatbed